Pengembangan Sistem Manajemen Stok Bahan Baku Roti Berbasis Web Menerapkan Metode Agile - Fuji Sudiro; Henri Septanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
PT. Nozawa Food Indonesia still faces challenges in raw material management due to stock recording processes that are carried out manually and are not yet digitally integrated. This study aims to develop a web-based inventory information system that implements the First In First Out (FIFO) method to support more organized raw material tracking. The research was conducted within the company environment using primary data obtained through observation and interviews. The system was developed using the Agile approach, allowing for iterative development from planning to evaluation. The system includes features such as stock-in and stock-out recording, minimum stock notifications, and stock reports accessible to relevant departments. The resulting system is expected to provide an efficient solution for stock documentation and support faster, data-based decision-making processes.